2009
DOI: 10.1111/j.1540-6288.2009.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Director Compensation and the Reliability of Accounting Information

Abstract: This paper studies the effect of incentive-based compensation on directors' monitoring of management. Using total accruals to measure the level of earnings management, I find that director stock option compensation is associated with higher levels of total accruals. I interpret this result to suggest that director stock options are more likely to align interests of directors with those of managers and that this convergence of interest manifests in lower transparency and reliability of financial information. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…Boumosleh (2009) found director stock options positively associated with earnings management and concluded that option compensation provides financial incentives for a director to fail to diligently monitor the financial reporting process. Bebchuk et al (2010) studied a duplicitous corporate practice that grants options to directors and CEOs when the stock prices were at their lowest value.…”
Section: Stock Option Compensationmentioning
confidence: 99%
See 3 more Smart Citations
“…Boumosleh (2009) found director stock options positively associated with earnings management and concluded that option compensation provides financial incentives for a director to fail to diligently monitor the financial reporting process. Bebchuk et al (2010) studied a duplicitous corporate practice that grants options to directors and CEOs when the stock prices were at their lowest value.…”
Section: Stock Option Compensationmentioning
confidence: 99%
“…Proponents of stock option compensation (Jensen 1993) argue that it aligns shareholders' and directors' interests, thereby motivating vigilant supervision of management to enhance the firm's stock price. However, a growing body of literature (Archambeault et al, 2008;Boumosleh, 2009;Cullinan et al, 2008) indicates that stock option compensation actually aligns the interests of directors with those of top managers, instead of shareholders, and thereby reduces director independence.…”
Section: Stock Option Compensationmentioning
confidence: 99%
See 2 more Smart Citations
“…The National Association of Corporate Directors (NACD) encourages greater equity (of at least 50%) in a director's compensation structure (NACD 2001) for two primary reasons. The NACD argues that greater equity compensation will better align directors' interests with those of shareholders by directing focus on long-term rather than short-term performance goals (Daily and Dalton 2002;Boumosleh 2009). However, the ultimate intent of greater equity compensation is to motivate directors to perform their governance responsibilities more effectively so that agency conflicts between management and shareholders are mitigated.…”
Section: Chapter Iv: Audit Committee Compensation and Meeting-beatingmentioning
confidence: 99%